Studi Insiden Energi Akibat Arc Flash Pada Subtation 6Dn PT. Chevron Pacific Indonesia - Sihar Panaili O.S; Amir Hamzah; Suwitno Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
PT. Chevron Pacific Indonesia is an exploration company oil and gas fields, which is one of the combustible material. Therefore, the risk in case of technical and non-technical disruptions that could generate sparks it will be very fatal. One interference that may cause a threat to life safety of the workers is the arc. Large arc energy generated depends on the working time safety system due to short-circuit current interruption, the incident energy calculations will be used as a reference in determining the appropriate safety equipment for workers. From the calculation results based on the IEEE 1584 2002 obtained the magnitude of the incident energy is varied, depend on fault clearing time of protection system.Keywords : Arc Flash, Incident Energy